Enhancing Employee Motivation: A TOPSIS-Based Decision Support System for Incentive Allocation through Performance Evaluation - Sutyawati, Yuke Subaikah; Daniawan, Benny (Department of Informatics Engineering, 2024)
Information technology is developing rapidly and has a significant role in various aspects, one of which is making decisions to evaluate employee performance. Employee performance assessment is an important activity and is often carried out by companies to determine employee performance in a certain period. A company's progress is greatly influenced by the good and bad of the system that is running. The decision support system can improve and influence the assessment of existing performance in the company. If the decision support system is inadequate, it can lead to errors in decision-making. This research was conducted at PT. App Inti provides enthusiasm and motivation to employees, and the company performs performance assessments every six months, which will influence the adjustment of employee salary increases. However, the current assessment process still uses simple methods and often experiences difficulties assessing performance, making the assessments less effective. Because errors and inaccuracies often occur during assessments, to make it easier for companies to make decisions and help solve these problems, a decision support system was designed using the TOPSIS method. The TOPSIS is a multi-attribute decision-making method often used to complete practical decisions. Then, the results can be considered and help the company determine a decision based on the alternatives and criteria that the company has decided. Then, the results of this research can help companies determine which employees are more visible during the assessment. Then, the TOPSIS ranking results are used to adjust salary increases that have been selected by the company, thereby helping companies make decisions more quickly.Keywords: Performance Appraisal, Decision Support System, TOPSIS